DO HUMAN RESOURCE PRACTICES, EMPLOYEE REMUNERATION AND EMPLOYEE BENEFITS HAVE SIGNIFICANT INFLUENCE ON THE RETENTION OF CHILDCARE TEACHERS IN THE CHILDCARE SERVICE INDUSTRY? - Philly Pek-Greer; Michelle Wallace; Yahya Al-Ansaari (Asian Academy of Management Journal, 2016)
This study investigates the impact of human resource practices, employee remuneration and employee benefits on childcare teachers' intentions to stay in the Singaporean workforce. This mixed methods study focuses on current qualified childcare teachers, their perspectives on human resource practices, employee remuneration and employee benefits in their workplaces and their intentions regarding whether to continue working in the childcare sector in Singapore. In the first phase of the study, which was qualitative, in-depth interviews were conducted with 21 current qualified childcare teachers. In the second phase of the study, which was quantitative, 202 current qualified childcare teachers in Singapore participated in a paper-based and web-based survey. The findings indicate that childcare teachers in Singapore want to be rewarded with fair human resource practices and employee wages are not the only dominant factor on the retention of childcare teachers in the Singaporean childcare industry. This study addresses a knowledge gap about childcare teacher retention in the childcare service industry in Singapore.